Neural Network based Dynamic Multicast Routing - Kojic, N.; Reljin, I.; Reljin, B. (Elektronika ir Elektrotechnika, 2013)
The Hopfield neural network is suggested for dynamic multicast routing in communication network of arbitrary topology and under variable traffic conditions. A new algorithm takes into account not only the most important parameters describing the actual network state (the network topology, link and router bandwidths, estimated link delays, and the traffic density), but also the history of link/router occupancy. The goal of the paper is to find the Pareto optimal path for multicast routing case and to avoid possible packets loss, due to heavy traffic. The effectiveness of the new routing algorithm has been verified under various network topologies and traffic conditions. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.3703